The impact of a pharmacist assisted clinic upon medication adherence and quality of life in mental health patients - Lizer MH; Parnapy Jawaid SA; Marsh W; Mogili L (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Objectives: To determine if a pharmacist assisted psychiatric clinic would improve adherence to medications and quality of life over 6 months. The primary study endpoints were the change from baseline in Medication Adherence Rating Scale (MARS), Brief Evaluation of Medication Influences and Beliefs (BEMIB), World Health Organization Quality of Life - BREF (WHOQOL-BREF) scales as well as hospitalizations and emergency room visits. Secondary endpoints included metabolic and physiologic parameters.Methods: A prospective, single-center study conducted at an outpatient psychiatric clinic. Subjects were required to attend 3 clinic visits (baseline, 3 and 6 months) with the pharmacist. Subject and medication histories were obtained at each visit. Subjects' records within the local health system were reviewed for emergency room visits and hospitalizations. Metabolic parameters were assessed at each visit.Results: Twenty-seven subjects enrolled and twenty subjects completed. Total MARS score at baseline and study end were 7.90 and 8.65, respectively. At baseline, 10 (50%) were nonadherent based on the BEMIB and 9 (45%) were nonadherent at 6 months. Statistically significant improvements were seen in 2 domains of the WHOQOL-BREF. Reductions in both ER visits and hospitalizations were achieved. There were significant improvements in total cholesterol and LDL.Conclusions: Improvements were seen in two domains of the WHOQOL-BREF - physical capacity and psychological well-being over the 6 month period. While improvements were seen in various rating scales, due to small sample sizes, these were insignificant improvements. Reductions in hospitalizations and ER visits were also seen during the study and up to 6 months post study. Statistically significant improvements were also seen in both total cholesterol and LDL. The lack of improvement in many of the study outcomes reflects the difficulty of the mental health population to adhere to treatment recommendations; but also underscores the need for continued research in this area. This pilot demonstrates the pharmacist's ability to provide comprehensive medication management services to the psychiatric outpatient.